2017
DOI: 10.1016/j.apsusc.2017.07.279
|View full text |Cite
|
Sign up to set email alerts
|

Atomic and electronic structure of a copper/graphene interface as prepared and 1.5 years after

Abstract: We report the results of X-ray spectroscopy and Raman measurements of as-prepared graphene on a high quality copper surface and the same materials after 1.5 years under different conditions (ambient and low humidity). The obtained results were compared with density functional theory calculations of the formation energies and electronic structures of various structural defects in graphene/Cu interfaces. For evaluation of the stability of the carbon cover, we propose a two-step model. The first step is oxidation… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 44 publications
0
11
0
Order By: Relevance
“…For nearly a decade, it has been controversial to suggest that graphene can be a protective layer for a Cu substrate against oxidation. Many groups reported that graphene accelerates oxidation of a Cu substrate by the catalytic cycle of water splitting into oxygen-containing groups at defect sites. This is not favorable for some applications, for example, copper interconnects. ,, From our results, the graphene/Cu 2 O hybrid structure significantly slows down the oxidation of Cu in the long term (>1 year), compared to bare Cu.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For nearly a decade, it has been controversial to suggest that graphene can be a protective layer for a Cu substrate against oxidation. Many groups reported that graphene accelerates oxidation of a Cu substrate by the catalytic cycle of water splitting into oxygen-containing groups at defect sites. This is not favorable for some applications, for example, copper interconnects. ,, From our results, the graphene/Cu 2 O hybrid structure significantly slows down the oxidation of Cu in the long term (>1 year), compared to bare Cu.…”
Section: Discussionmentioning
confidence: 99%
“…Graphene has been recognized as an anticorrosion barrier because of its impermeability to gases. Thus, it may be an excellent candidate for protecting copper, as an interconnecting material, from oxidation. Previous observations have shown that graphene is capable of protecting copper from oxidation at short time scales (<1 day), even at increased annealing temperatures (>200 °C), but it promotes corrosion after long exposure to ambient conditions (>several months) . With further investigation, an anticorrosion property can be achieved by commensurate graphene coating on a Cu(111) surface .…”
mentioning
confidence: 98%
“…The position of C 1s line (right inset in Figure 2b) at 284.4 eV and its form are attributed to pure sp 2 carbon, described in the literature as a “free‐standing” non‐interacting graphene, [ 32 ] which is not contaminated and has no additional bonds often observed for the hydrocarbon derived samples. [ 35–38 ] At the same time, the state of the catalyst appears to correspond to a pure unoxidized copper, Cu 0 , [ 39 ] as supported by Cu 2p (932.7 eV) in Figure 2b (the left inset) and Auger Cu LMM lines ( E K = 918.7 eV, see Figure S1, Supporting Information). Minor contaminations revealed by weak O 1s (core level in Figure S1, Supporting Information) line in the XPS spectrum (obtained without vacuum sample annealing) were analyzed by the near edge X‐ray absorption fine structure (NEXAFS) spectroscopy.…”
Section: Resultsmentioning
confidence: 99%
“…Despite the promising findings summarised in Table 1, the role of graphene as a corrosion inhibition coating is often disputed, especially its long-term performance. For example, graphene-based coatings on copper have shown good long term stability in humid environments for up to 1.5 [50] or 2.5 years [51] and Scardamaglia et al [52] have shown that graphene-based coatings act as effective barriers at high temperatures and prevent the corrosion of the underlying copper. However, it has also been argued that the oxygen trapped during formation of the graphene-based layers gives rise to oxidation of the copper substrate [53], while Schriver et al [54] have demonstrated that graphene promotes more extensive corrosion than that observed with the uncoated copper over a long-term period.…”
Section: Graphene-based Metallic-like Coatingsmentioning
confidence: 99%